If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(3x+1)=6(8-6x)
We move all terms to the left:
3(3x+1)-(6(8-6x))=0
We add all the numbers together, and all the variables
3(3x+1)-(6(-6x+8))=0
We multiply parentheses
9x-(6(-6x+8))+3=0
We calculate terms in parentheses: -(6(-6x+8)), so:We get rid of parentheses
6(-6x+8)
We multiply parentheses
-36x+48
Back to the equation:
-(-36x+48)
9x+36x-48+3=0
We add all the numbers together, and all the variables
45x-45=0
We move all terms containing x to the left, all other terms to the right
45x=45
x=45/45
x=1
| 8x+7+3(4x+5)=2x+184 | | 25–3x=4 | | 2x^2+28x=-192 | | T-6.38;t=8.006 | | S=19v2 | | [2d-3[=19 | | -2x^2+12^2-10=0 | | -2p+21=11 | | 3.652-a;a=1.41 | | 3x-9=8-4 | | 0=6x^-96 | | 4^(5x-7)=3^(9x-6) | | 4(m-8)=-4 | | R+15.9;r=0.214 | | `(3x+5)(3x-5)=(9x-25)` | | 5x^2—2x=16 | | 24.84-h;h=22.7 | | 5│7x+6│=40 | | 7x+6=457x+6=-45 | | (2x-5)(2x-15)=4x^2+5x | | -12/2+m=2 | | G(x)=5x2-4x | | 14.2=2t | | -12+m/2=2 | | 180=126+22+x | | √5x2-5x+√5=0 | | (2x-5)(2x-15)=4x^2-5x | | 2-4m=50 | | 18x+7x=+3-5 | | 3/4x+2/4=0.25 | | 31=11-5m | | 18x-3=-7x-5 |